Prediction of Early Death in Patients With Sepsis-Associated Coagulation Disorder Treated With Antithrombin Supplementation. (December 2018) - Iba, Toshiaki; Arakawa, Makoto; Ohchi, Yoshifumi; Arai, Takao; Sato, Koichi; Wada, Hideo; Levy, Jerrold H.
For success in clinical trials, eliminating inclusion of patients with irreversible recovery is important. The purpose of this study was to identify the patient population who do not survive for more than 3 days. A total of 449 patients with sepsis suspected of having disseminated intravascular coagulation (DIC) and treated with antithrombin were examined. The patient characteristics, baseline sequential organ failure assessment (SOFA) score, DIC score, and hemostatic markers were retrospectively analyzed in relation to early death (died within 3 days). At the end of day 3, a total of 419 patients had survived and 30 patients had died. A logistic regression analysis revealed a significant association between early death and the baseline prothrombin time-international normalized ratio PT-INR ( P <.05) and the total SOFA score ( P <.01). In contrast, neither the platelet count, fibrinogen/fibrin degradation products, and antithrombin activity nor the DIC score was associated with early death. Although the accuracy for predicting early death defined by either baseline PT-INR of ≥1.57 or total SOFA score of more than 13 was not high enough, that of "high-risk of early death (PT-INR ≥ 1.57 and SOFA score ≥ 13)" was 83.5%. Furthermore, the negative predictive of this category was 96.0%. The baseline SOFA score and PT-INR were associated with early death among patients with sepsis-associated coagulation disorders. Patients who do not meet the "high-risk of early death" criteria were likely to survive for more than 3 days and therefore should be considered for future therapeutic clinical trials.